Resonant electron tunneling in GaN/Ga1-x AlxN(0001) strained structures with spontaneous polarization and piezoeffec; Physics of the Solid State; Vol. 43, iss. 3 - Grinyaev S. N. Sergey Nikolaevich (Low-Dimensional Systems And Surface Physics, 2001)
Title screen